AKR1A1 Variant Associated With Schizophrenia Causes Exon Skipping, Leading to Loss of Enzymatic Activity - Iino, Kyoka; Toriumi, Kazuya; Agarie, Riko; Miyashita, Mitsuhiro; Suzuki, Kazuhiro; Horiuchi, Yasue; Niizato, Kazuhiro; Oshima, Kenichi; Imai, Atsushi; Nagase, Yukihiro; Kushima, Itaru; Koike, Shinsuke; et al. (Frontiers in Genetics, 2021)
Schizophrenia is a heterogeneous psychiatric disorder characterized by positive symptoms such as hallucinations and delusions, negative symptoms such as anhedonia and flat affect, and cognitive impairment. Recently, glucuronate (GlucA) levels were reported to be significantly higher in serum of patients with schizophrenia than those in healthy controls. The accumulation of GlucA is known to be related to treatment-resistant schizophrenia, since GlucA is known to promote drug excretion by forming conjugates with drugs. However, the cause of GlucA accumulation remains unclear. Aldo-keto reductase family 1 member A1 (AKR1A1) is an oxidoreductase that catalyzes the reduction of GlucA. Genetic loss of AKR1A1 function is known to result in the accumulation of GlucA in rodents. Here, we aimed to explore genetic defects in AKR1A1 in patients with schizophrenia, which may result in the accumulation of GlucA. We identified 28 variants of AKR1A1 in patients with schizophrenia and control subjects. In particular, we identified a silent c.753G>A (rs745484618, p. Arg251Arg) variant located at the first position of exon 8 to be associated with schizophrenia. Using a minigene assay, we found that the c.753G>A variant induced exon 8 skipping in AKR1A1, resulting in a frameshift mutation, which in turn led to truncation of the AKR1A1 protein. Using the recombinant protein, we demonstrated that the truncated AKR1A1 completely lost its activity. Furthermore, we showed that AKR1A1 mRNA expression in the whole blood cells of individuals with the c.753G>A variant tended to be lower than that in those without the variants, leading to lower AKR activity. Our findings suggest that AKR1A1 carrying the c.753G>A variant induces exon skipping, leading to a loss of gene expression and enzymatic activity. Thus, GlucA patients with schizophrenia with the c.753G>A variant may show higher GlucA levels, leading to drug-resistant schizophrenia, since drug excretion by GlucA is enhanced.